A NEW ERA IN COMBATING CYBERCRIME: HOW THE AUTOMATION AND GOVERNANCE OF MED 2.0 DRIVE LOSS REDUCTION AND THE DETERRENCE OF FINANCIAL FRAUD IN BRAZIL (REMUNOM, 2026)
The contemporary landscape of financial transactions in Brazil is characterized by the rise of digital illicit acts, whose complexity is amplified by continuous criminal technological innovation. Against this backdrop, the central objective of this analysis is to examine the Special Return Mechanism (MED) and its evolution, MED 2.0, investigating to what extent automation and the improvement of institutional governance enhance the probability and speed of asset recovery and deter new types of fraud, thereby strengthening the resilience of the instant payment ecosystem. The methodology consists of qualitative, descriptive-interpretative documentary research. Data collection was based on the systematic reading of official documents, involving the extraction of statistics and key concepts, followed by thematic categorization and content analysis. Results indicate that MED 2.0 represents a promising evolution by extending the freezing of funds to multi-layer accounts, integrating risk engines, and strengthening inter-institutional cooperation. However, its effectiveness is conditioned on the proper calibration of operational limits and deadlines, guaranteed data quality, procedural transparency, user education, and strict compliance with the General Personal Data Protection Law (LGPD). It is concluded that the improved mechanism has significant potential to reduce the expected value of financial crimes, increasing the resilience and security of the entire Pix payment system.